Logic of action and capabilities contexts in community educational work. A research in an alpine valley - Valenzano, Nicolò (Formazione & insegnamento, 2020)
Community work, understood as a proposal for a new model of community welfare and social intervention, has recently become a topic of great interest in the social and educational fields. In this perspective, community development is an approach that promotes the construction of social bonds within a given territorial context, in order to improve the economic, social and cultural conditions of the community and the people who live in it. This paper starts from an empirical research that analyses community work in a marginal areas around Monviso to show, firstly, the action strategies necessary to promote competent communities. Secondly, I argue that emphasizing community development means organizing educational community work actions that focus in particular on building capabilities contexts. To understand this concept, I will try to connect the Capability Apporach with the theoretical framework of Community Development, in particular the concept of empowerment and empowering setting. The results of the overall research and those specifically reported in this paper offer an interpretative and transformative contribution to the community educational work and allow a more effective accountability.